Diseño de un sistema de gestión integrado basado en la NTC ISO 14001:2004 NTC OOHSA 18001: 007 siguiendo los lineamientos establecidos por el PMI® para las fases de iniciación y planificación en la unidad de negocio de transporte fluvial de carga en Cimecel S.A.S. (2013)
This paper presents the most relevant results of the DESIGN OF AN INTEGRATED MANAGEMENT SYSTEM, BASED ON NTC ISO 14001: 2004. NTC OHSAS 18001: 2007, FOLLOWING THE GUIDELINES FOR THE PMI® FOR THE STAGES OF INCIATION AND PLANNING, IN THE UNIT OF TRANSPORTATION FLUVIAL OF CARGO IN CIMECEL S.A.S. For this, the description of the documentation of each of the elements of the planning of the rules, of the methodology carried out to infer the strategic planning of the company in reference to this business unit, as well as a description of the procedures for identifying hazards, assessing risks and determining controls, identifying aspects and assessing impacts, identifying legal and other requirements, and finally, objectives and proposed programs.